Adaptasi Digital Marketing berbasis Website untuk Produk UMKM Fatikha Sweet Honey - Haryadi, Toto; Ulumuddin, Dimas Irawan Ihya'; Prabowo, Dwi Puji; Ihwan, Afif Mas’udi (Universitas PGRI Semarang, 2022)
Honey is one of health supplements which bought by people to prevent Covid-19 symptoms. This is an opportunity for Fatikha Sweet Honey to introduce its products. However, the currently applied digital marketing strategy only focus on Facebook and Instagram media, which rarely get a response from consumers. It needs digital marketing media which can present a variety of product information such as: photos, benefits, variants, how to order, and so on. Based on these considerations, the website becomes a right digital marketing medium. This study focuses on adapting the website as a medium to introduce and sell honey products. The study used qualitative methods, supported by data searches through indirect interviews, observation, and literature studies. Website adaptation using MDLC. The result is a website as main media for promoting and selling Fatikha Sweet Honey products. The output of this research is expected to be useful for increasing sales of it and can be further developed into a marketplace application.